IMF fairness: Calibrating the policies of the International Monetary Fund based on distributive justice. (September 2022) - Daoud, Adel; Herlitz, Anders; Subramanian, S.V.
Highlights: A review of the literature shows that IMF programs affect children adversely. Distribute justice provides a foundation for theorizing on trade-offs between macroeconomics and population health. A combination of sufficientarianism and causal inference formalizes the trade-off between macroeconomics and population health. Five principles define IMF fairness. A simulation exemplifies how IMF fairness can be measured. Abstract: The International Monetary Fund (IMF) provides financial assistance to its member countries in economic difficulties but at the same time requires these countries to reform public policies. In several contexts, these reforms have been at odds with population health and material living standards. While researchers have empirically analyzed the consequences of IMF reforms on health, no analysis has yet identified under what conditions tradeoffs between consequences for populations and economic outcomes would be fair and acceptable. Our article analyzes and identifies five principles to govern such tradeoffs and thus define IMF fairness. The article first reviews existing policy-evaluation studies, which on balance show that IMF policies, in their pursuit of macroeconomic improvement, frequently produce adverse effects on children's health and material living standards. Secondly, the article discusses four theories from distributive ethics—maximization, egalitarianism, prioritarianism, and sufficientarianism—to identify which is most compatible with the IMF's core mission of improving macroeconomic conditions, while at the same time balancing the consequences for population outcomes. Using a distributive justice analysis of IMF policies, we argue that sufficientarianism constitutes the most compatible theory. Thirdly, the article formalizes IMF fairness in the language of causal inference. It also supplies a framework for empirically measuring the extent to which IMF policies fulfill the criteria of IMF fairness, using observational data.